A REPLY. - Littleton, A. C. (The Accounting Review, 1953)
Abstract The article presents the author's views on an article previously published in the October issue of the Accounting Review, entitled "Limitations on the Significance of Invested Cost." Accounting is progressive; it clearly has shown that tendency in the marked development, strange to ancient usages, of its industrial and managerial aspects. A similarly far-reaching progressive development was slow to appear in auditing although that is the professional area. Still less has accounting shown a full measure of progressive development of its interpretative aspects, i.e., in the collateral work of making the results of technical accounting processes understood by more and more people. Perhaps index number adjustments are intended to constitute an advance in the latter area. And few indeed will take exception to this or any other interpretative endeavor, provided the effort does not meanwhile emasculate the well-known and still very useful data that emerge from the normal accounting process. It could hardly be progress if its price were the submerging of accounting's basic information or of yielding anything on the objectivity issue. It is not likely to prove to be progress merely to develop the new and wider areas of data to be brought within the framework of double entry, following ever farther the lead in this respect of fund accounting and standard cost accounts. There must be limits to accounting adaptability as there are limitations in the significance of "invested cost." A permanent cleavage between balance sheet and income statement (between objectivity determined real and nominal accounts) can not properly be called "progressive."